A Randomised Controlled Trial On Hypolipidemic Effects Of Nigella Sativa Seeds Powder In Menopausal Women. - Siti Aisyah Abd Ghafar; Ramlah Mohamad Ibrahim; Nurul Syima Hamdan; Rozi Mahmud; Mustapha Umar Imam; Suraini Mohd Saini; Saiful Nizam Abd Rashid; Latiffah Ab Latiff; Maznah Ismail (BioMed Central Ltd., 2024)
Non-Indexed Publication